PENGARUH CASH CONVERSION CYCLE, STOCK CONVERSION PERIOD, AVERAGE COLLECTION PERIOD, PAYABLE DEFERRAL PERIOD, DAN NET RECEIVABLE PERIOD TERHADAP KINERJA PERUSAHAAN DENGAN CURRENT RATIO, LEVERAGE DAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2021) - Miftahuddin, Muhammad; Sampurno, Raden Djoko (Diponegoro Journal of Management, 2023)
ABSTRACT This study aimed to examine the effect of Cash Conversion Cycle (CCC), Stock Conversion Period (SCP), Average Collection Period (ACP), Payable Deferral Period (PDP), and Net Receivable Period (NRP) on the performance of manufacturing companies listed on the Indonesia Stock Exchange. Company performance was measured by Return on Assets (ROA) which described accounting-based performance and the Tobin's Q (TQ) ratio which described market-based performance. This study also added Current Ratio (CR), Leverage (LEV), and Firm Size (SZ) as control variables. The population used in this study was manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015 to 2021 period. The number of samples used was 120 companies which were taken using a purposive sampling method. The analytical method used was panel data regression with the addition of the Robust Standard Error procedure to overcome the heteroscedasticity problem in the Fixed Effect Model (FEM). The results showed that CCC and SCP had a significant negative effect on both measures of firm performance. PDP was found to have a significant negative effect on ROA, but a significant positive effect on market size. ACP had a negative effect on both measures of firm performance, but not supported by statistical significance. NRP had an insignificant positive effect on ROA and an insignificant negative effect on TQ. In addition, Firm Size (SZ) had a negative effect on ROA and TQ. CR had a positive effect on both measures of firm performance and LEV was found to have a significant negative effect on ROA and an insignificant positive effect on TQ.